2019
DOI: 10.1002/mc.23101
|View full text |Cite
|
Sign up to set email alerts
|

Small nucleolar RNA host gene 1 promotes development and progression of colorectal cancer through negative regulation of miR‐137

Abstract: Small nucleolar RNA host gene 1 (SNHG1) is critical in the progression of cancers. However, the mechanism by which SNHG1 regulates the progression of colorectal cancer (CRC) remains unclear. Expressions of SNHG1 and miR‐137 in CRC tissues and cell lines were evaluated by quantitative real‐time polymerase chain reaction. A luciferase reporter gene assay was conducted to investigate miR‐137 target. Additionally, RNA pull‐down assay was performed to explore the physical association between miR‐137, SNHG1, and RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
4
16
0
Order By: Relevance
“…However, this previous research failed to figure out the specific target mRNA to form a complete lncRNA-miRNA-mRNA axis. MiR-137 is a novel microRNA involved in colorectal cancer [30,38] and Notch-1 plays an important role in promoting the progression of CRC [39]. Our study proved that miR-137 directly targets at Notch-1 by binding with its 3'-UTR, and DSCAM-AS1 regulates the miR-137/Notch-1 axis.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…However, this previous research failed to figure out the specific target mRNA to form a complete lncRNA-miRNA-mRNA axis. MiR-137 is a novel microRNA involved in colorectal cancer [30,38] and Notch-1 plays an important role in promoting the progression of CRC [39]. Our study proved that miR-137 directly targets at Notch-1 by binding with its 3'-UTR, and DSCAM-AS1 regulates the miR-137/Notch-1 axis.…”
Section: Discussionsupporting
confidence: 51%
“…Although the expression and function of DSCAM-AS1 have been reported in previous studies in several tumors, the potential mechanisms involved have not been clarified. By predicting with miRcode, we found that miR-137, a novel microRNA involved in cancer 30 - 32 was a potential target of DSCAM-AS1. Recently studies showed that miR-137 might participate in the progression of CRC by directly targeting at EZH2 32 , TCF4 31 and YBX1 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence supported the involvement of miR-137 in cancer biology [ 33 ]. MiR-137 has been found to interact with long non-coding RNA (lncRNA) small nucleolar RNA host gene 1 (SNHG1) in the tumorigenesis of colorectal cancer (CRC) [ 34 ]. Moreover, miR-137 has been reported to be abnormally expressed in cancer samples and exhibited anti-cancer potential in ovarian cancer [ 35 ] and gastric cancer [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the difference of SNHG1 was signi cantly higher than that of DIO3OS. There was literature indicating the upregulation of SNHG1 in thyroid cancer [14], non-small cell lung cancer (NSCLC) [15], colorectal cancer [16,17], but SNHG1 was not studied in bladder cancer. Next, RNA-FISH showed high SNHG1 expression in bladder cancer tissues compared with adjacent normal tissues (Fig.…”
Section: Snhg1 Was Highly Expressed In Bladder Cancer Tissues and Assmentioning
confidence: 99%